(untitled) (Педагогіка вищої та середньої школи, 2009)
On the grounds of the analysis of Ukrainian scientists ‘ works of the beginning of the XX century the process of formation of our country ethnodesign theory & history conception is retraced. Special attention is paid to the problem of Ukrainian folk art national forms definition.